Peningkatan Kemampuan Berbahasa Melalui Metode Bermain Peran Pada Anak Didik Kelompok B Semester 1 TK Dharma Wanita 3 Botoreco Kecamatan Kunduran Kabupaten Blora Tahun Pelajaran 2015/2016 - YATMININGSIH, YATMININGSIH; , Drs. Sutan Syahrir Zabda, SH,MH (2015)
This study aims to determine the increase proficiency in the 1st half of children in group B TK Dharma Wanita 3 Botoreco District of Kunduran using methods play a role. Subject implementation of the action is a child group B TK Dharma Wanita 3 Kunduran totaling 15 children consisting of 5 girls and 10 boys. This type of research using Action Research (CAR). The research was conducted in two cycles, each cycle consisting of two rounds. Data collection methods used were observation, interviews and documentation. The research result is an increase in child language skills using role play. The increase in child language skills are as follows: increase children's language ability in a row of prasiklus 57.5% and then to 69.4% in the cycle, I rose to 88.1% in Cycle II